2000
DOI: 10.1139/l00-048
|View full text |Cite
|
Sign up to set email alerts
|

Design and evaluation of a wedge-type anchor for fibre reinforced polymer tendons

Abstract: The development of a wedge-type anchorage system for fibre reinforced polymer (FRP) tendons, as part of an overall corrosion-free post-tensioning system, is outlined in this paper. A stainless steel anchor is described, and results from numerical models and load tests to evaluate its behaviour under loads from anchor set, as well as static and repeated tendon tension, are presented. An alternative wedge-type anchorage system made from ultra-high performance concrete is also described. It is shown that, althoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(14 citation statements)
references
References 2 publications
0
13
0
1
Order By: Relevance
“…However, no further information was provided regarding the selected cyclic load history and fatigue acceptance criteria. In other studies, fatigue tests were performed according to the procedure recommended by the Post-Tensioning Institute (PTI 1985), which is typically used for steel tendons (Sayed-Ahmed and Shrive 1998; Campbell et al 2000;Taha and Shrive 2003;Elrefai et al 2007). These studies concluded that the fatigue performance of the anchors could fulfil the requirements of PTI 1985.…”
Section: Fatigue Tests On Mechanical Wedge-barrel Anchorsmentioning
confidence: 99%
“…However, no further information was provided regarding the selected cyclic load history and fatigue acceptance criteria. In other studies, fatigue tests were performed according to the procedure recommended by the Post-Tensioning Institute (PTI 1985), which is typically used for steel tendons (Sayed-Ahmed and Shrive 1998; Campbell et al 2000;Taha and Shrive 2003;Elrefai et al 2007). These studies concluded that the fatigue performance of the anchors could fulfil the requirements of PTI 1985.…”
Section: Fatigue Tests On Mechanical Wedge-barrel Anchorsmentioning
confidence: 99%
“…Considering the aforementioned issues, this study, for the first time, proposes the application of prestressed CFRP rods for strengthening bridge connections. Thus far, different mechanical anchorages have been developed for post-tensioned CFRP rods (Sayed-Ahmed and Shrive 1998; Campbell et al 2000;Al-Mayah et al 2005;Al-Mayah et al 2006aSchmidt et al 2010;Schmidt et al 2011;Schmidt et al 2012). In these studies, the proposed mechanical anchorages consisted of a barrel with a conical hole inside, and split or integrated wedges holding the CFRP rod.…”
Section: Knowledge Gap and Objectives Of The Studymentioning
confidence: 99%
“…Zhuge (2010) also evaluated the stress of a conical barrel based on the mechanical behavior of the wedge-type anchor for CFRP tendons. Campbell et al (2000) observed the performance and changes in the wedge for individual and cyclic loads based on the wedge-type stainless steel anchorage system using FRP tendons [ 22 , 23 , 24 , 25 , 26 ]. Thus, most existing studies have focused on the wedge-type anchorage system using steel strands [ 27 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%